Effects of Fixed and Removable Functional Appliances on Skeletal and Dentoalveolar Structures - Gökmen Kurt; Aslı Baysal; Cemal Şişman; Çağlar Sakin (Galenos Yayinevi, 2010)
Aim:To compare the skeletal and dentoalveolar changes after Herbst and Twin-block treatment in Class II division 1 patients.Subjects and Methods:Cephalomet-ric radiographs of 20 patients treated with Herbst and Twin-block appliance and 10 untreated subjects are used. Totally 29 maxillary, mandibular, maxillomandibu-lar and dentoalveolar measurements were achieved. Paired sample t-test was used to determine intra-group differences and one way analysis was used to determine inter-group differences.Results:After Herbst appliance therapy, an increase in mandibular corpus length and mandibular incisor protrusion and decrease in ANB, overjet and overbite were observed. In Twin-block group, significant increases were observed in all mandibular measurements except nasion perpendicular to pogonion. A point moved anteriorly and effective middle face length increased. Increases were observed in effective mandibular length and in all measurements that show mandibular sagittal (Go-Gn) and vertical (Co-Go, S-Go) dimension. Only maxillary nasal plane to upper first molar length that shows maxillary molar eruption increased in dental measurements. Comparison of groups showed that both appliances decreased ANB angle and overjet. In Herbst group, significant differences were observed in effective middle face dimension and distance of Nasion perpendicular to A point, compared with the Control group. No significant difference was observed in other mandibular and dentoalveoler measurements between the groups.Conclusions:Twin-block appliance showed more skeletal changes and the Herbst appliance showed skeletal and dental changes in our study. The appliances exhibited similar effects compared with the Control group.